SELF CONTROL AND PARENTING STYLE OF ACADEMIC PROCRASTINATION IN VOCATIONAL HIGH SCHOOL STUDENTS - Rahayu Dewany; Nurfarhanah; Megaiswari Biran Asnah; Rezki Hariko (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research is a quantitative research with a correlational design. Research with this correlational design involves collecting data to identify the level of correlation between two or more variables(Santoso & Madiistriyanto, 2021). Research by typecorrelational quantitative which aims to test how big the relationship between research variables is by using multiple regression analysis techniques to test the relationship of two independent variables to one dependent variable(Siregar, 2014). The population in this study were all students in class X and XI of SMKN 3 Padang for the 2022/2023 academic year with a total of 804 students. While the sampling in research using techniquesproportional Stratified Random Sampling,This technique is used for random and stratified sampling of members of the population. The sampling process begins with identifying the population based on class groups using the Slovin formula(Joseph 2013)so that as many as 267 students from class X and XI were found as samples in this study. From this study, it can be concluded that self-control and parenting style of students at SMKN 3 Padang are high, while student academic procrastination is moderate. The results of the correlation coefficient analysis using multiple regression techniques show that there is a relationship between self-control and academic procrastination of 36.7%, while there is no correlation between self-control and academic procrastination. the relationship between parenting style and students' academic procrastination with a value of 0.14%. Therefore it can be seen that students' academic procrastination is only influenced by self-control. Students with low self-control will have high academic procrastination behavior, while students with high self-control will tend to have low academic procrastination.